Аналіз перешкод у реалізації інноваційної активності персоналу підприємств в умовах глобальних змін - Семикина, М. В.; Федунець, А. Д.; Semikina, M.; Fedunets, A. (НАПКС, 2014)
В процесі аналізу доведено, що зниження інноваційної активності персоналу підприємств слід пов’язувати з комплексом соціодемографічних та соціально-економічних чинників, трансформацією зайнятості, яка не має інноваційного характеру. Визначено негативні тенденції у стимулюванні праці, що руйнують мотивацію до творчості. Розкрито сутність кризових явищ у розвитку науки, сфері освітньо-професійного розвитку населення, які погіршують якість кадрового забезпечення інноваційної діяльності в Україні. In the course of the analysis has been proved that decrease in innovative activity of the personnel of the enterprises should be connected with a complex the social-demographic and socio-economic factors, transformation of employment which has no innovative character. Negative tendencies in the work incentives which destroy motivation to creativity have been defined. The essence of the crisis phenomena in the science development, sphere of educational and professional development of the population which worsen the quality of staffing of innovative activity in Ukraine is revealed.
The analysis of the obstacles in realization of innovative activity of the personnel of the enterprises in the conditions of global changes
Keywords: інновації; інноваційна активність; стимулювання праці; освітньо-професійний розвиток; мотивація творчості; якість кадрового забезпечення; innovations; innovative activity; work incentives; educational and professional development; motivation of creativity; quality of staffing